Factors associated with instrumental support in transitional care among older people with chronic disease: a cross-sectional study - Min Cui; Jianing Hua; Xiaoliu Shi; Wenwen Yang; Zihan Geng; Xiangyun Qian; Guiling Geng (BMC, 2022)
Abstract Background Instrumental support, which is defined as practical, tangible, and informational assistance extended to patients, is crucial for older people in transition. However, little is known about instrumental support in transitional care. Thus, the aim of this study was to evaluate the instrumental support of older people in transitional care. Methods This cross-sectional study was conducted using the Questionnaire of Instrumental Support in Transitional Care (QISCT) to collect data from 747 older people in China from September to November 2020. Survey items consisted of a sociodemographic characteristics questionnaire and the QISCT. Multiple regression analyses were conducted to examine the association between independent variables and the QISCT scores. Results The total score of the QISCT was 39.43 (± 9.11), and there was a significant gap between the anticipated support and received support. The satisfaction of instrumental support was low. Multiple regression analyses showed that educational level, the number of intimate relationships, monthly family income, monthly costs of transitional care, diabetes, and chronic obstructive pulmonary disease were associated with instrumental support in transitional care. Conclusions To cope with the burden caused by chronic disease, the government and transitional care teams should establish a demand-oriented transitional care service model and pay more attention to helping older people obtain adequate and satisfactory instrumental support.